2020
DOI: 10.2196/preprints.17750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptance and Commitment Therapy Delivered via a Mobile Phone Messaging Robot to Decrease Postoperative Opioid Use in Patients With Orthopedic Trauma: Randomized Controlled Trial (Preprint)

Abstract: BACKGROUND Acceptance and Commitment Therapy (ACT) is a pragmatic approach to help individuals decrease avoidable suffering and pain. OBJECTIVE To evaluate the effects of Acceptance and Commitment Therapy (ACT) delivered via an automated mobile messaging robot on postoperative opioid utilization and patient reported outcomes (PROs) in orthopaedic trauma patients who underwent operative interven… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The identified studies (n=29) were mostly conducted in the USA (n=10), Sweden (n=6), and the UK (n=6). The studies included a diverse sample of adults (n=22), college students and young adults (n=4), anonymous users (n=2), and adolescents (n=1) ( 28 33 , 41 , 73 94 ). Eight studies reported on the ethnicity of the participants ( 30 , 32 , 41 , 74 , 76 , 77 , 80 , 83 ), and in most of the studies between 31% and 91% of the participants identified as White.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The identified studies (n=29) were mostly conducted in the USA (n=10), Sweden (n=6), and the UK (n=6). The studies included a diverse sample of adults (n=22), college students and young adults (n=4), anonymous users (n=2), and adolescents (n=1) ( 28 33 , 41 , 73 94 ). Eight studies reported on the ethnicity of the participants ( 30 , 32 , 41 , 74 , 76 , 77 , 80 , 83 ), and in most of the studies between 31% and 91% of the participants identified as White.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included a diverse sample of adults (n=22), college students and young adults (n=4), anonymous users (n=2), and adolescents (n=1) ( 28 33 , 41 , 73 94 ). Eight studies reported on the ethnicity of the participants ( 30 , 32 , 41 , 74 , 76 , 77 , 80 , 83 ), and in most of the studies between 31% and 91% of the participants identified as White. The studies focused on a population with moderate psychiatric symptoms including depression, anxiety, obsessive-compulsive disorder (OCD), insomnia, stress, body dysmorphic disorder (BDD), opioid misuse, social anxiety disorder (SAD), and bipolar personality disorder.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations